Comparative analysis of minimally invasive endoscopic versus conventional open posterior brucellosis lesion removal in the treatment of brucellosis spondylitis - Siyiti, Sikandaer; Hang, Lin; Siyiti, Adila; Jiangtao, Sui (Frontiers in Medicine, 2025)
ObjectiveThis study aims to evaluate the clinical effectiveness of minimally invasive versus conventional open posterior methods for the excision of brucellosis lesions in the context of spondylitis treatment. The findings are intended to inform and guide clinical practice.MethodsForty-three patients with brucellosis spondylitis who attended our hospital from January 2020 to June 2023 were selected and divided into minimally invasive endoscopic brucellosis lesion removal (group A) n = 18 and traditional open lesion removal group (group B) n = 25 according to the operation type. All patients were given antibiotic treatment before operation. Analyze the relevant clinical indicators.Results① There were no statistically significant differences (p > 0.05) between the two groups in terms of age, gender, body mass index (BMI), medical history, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), procalcitonin (PCT), D-dimer, hemoglobin (Hb), visual analog scale (VAS) score, Oswestry Disability Index (ODI) score and recurrence rate. ② The operation time (p < 0.012), intraoperative blood loss (p < 0.012), and postoperative hospital stay (p < 0.012) in group A were significantly shorter than those in group B, and the differences between the two groups were statistically significant (p < 0.05). No significant differences were observed in the remaining outcome measures.ConclusionThe results of this study showed that minimally invasive endoscopic brucellosis lesion removal could achieve the same efficacy as compared with traditional open posterior lesion removal, but minimally invasive surgery has the advantages of shorter operative time, lower intraoperative hemorrhage and more obvious advantages in postoperative rehabilitation, etc., which makes it clinically feasible and effective procedure.